The Effect Of Viral Marketing And Celebrity Endorsers On Purchasing Decisions For Somethinc X NCT Dream Skincare At TikTok Shop - Nindy Selvya Dewi; Helda Melinda; Muhamad santoso (Al-Makki Publisher, 2024)
The development of the internet shows that there is growth in more and more internet users worldwide, and Indonesia is one of them. However, in modern times this has spread widely to the economic and entrepreneurial fields, so the term E-commerce or online trading has emerged to meet daily needs such as Tiktok Shop. The success of Tiktok Shop in Indonesia is due to the way business actors change promotional strategies using viral marketing and celebrity endorsers to get public attention and viral news on social media. This study aims to determine the effect of viral marketing and celebrity endorsers on purchasing decisions for something X NCT Dream skincare at TikTok Shop. The method used is a Quantitative approach with the type of associative research is data collection by distributing questionnaires using an online system via Google form with as many as 200 respondents. Data processing was then analyzed using IBM SPSS 25 Version for Windows. The data analysis used is Multiple Linear Analysis. All hypotheses show significance. The conclusion is that the influence of viral marketing and celebrity endorsers has a significant and positive effect on purchasing decisions for something X NCT Dream skincare at TikTok Shop.